(untitled) (Journal of the Bangladesh Agricultural University, 2012)
A field experiment was carried out to study the effects of inorganic nitrogenous fertilizer and organic cowdung manure on growth and yield of carrot. Three different levels of urea along with three different levels of cowdung were employed in the investigation following randomized complete block design. The result revealed that the application of 150 kg N ha-1 as urea was found suitable for maximum gross and marketable yield (47.35 t ha-1 and 39.0 t ha-1, respectively), while 15 t cowdung ha-1 showed better gross and marketable yield (38.13 t ha-1 and 30.42 t ha-1 , respectively). Regarding the combined effect, the combination of 150 kg N ha-1 and 15 t cowdung ha-1 resulted in the best performance in gross and marketable yields (51.22 t ha-1 and 43.41 t ha-1, respectively). The net return (TK. 211142 ha-1) and benefit cost ratio (4.61) were maximum in the treatment combination of 150 kg N ha-1 in the form of urea and 15 t cowdung ha-1. DOI: http://dx.doi.org/10.3329/jbau.v10i1.12012 J. Bangladesh Agril. Univ. 10(1): 913, 2012